The Contribution of Islamic Education in Instilling Noble Moral Values as a Solution to Social Problems in the Era of Globalization - Sri Mulyani; Kartini Kartini (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2025)
This study aims to examine the contribution of Islamic education in instilling noble moral values as a solution to social diseases in the era of globalization. Globalization has brought significant changes in social life, including the emergence of various social problems such as moral degradation, juvenile delinquency, violence, and social inequality. Islamic education is considered to have a strategic role in addressing these issues through the internalization of moral and ethical values based on Islamic teachings. This research employs a library research method by analyzing various relevant sources, including books, scientific journals, research reports, and authoritative academic publications related to Islamic education, morality, and social problems. The data were analyzed descriptively and analytically to identify patterns, concepts, and perspectives regarding the role of Islamic education in moral development. The results of the study indicate that Islamic education contributes significantly to shaping individual character by emphasizing faith, piety, moral responsibility, and social awareness. Through systematic moral education, Islamic education is able to provide preventive and corrective solutions to social diseases. The study concludes that strengthening Islamic education is essential in building a morally sound society capable of facing the challenges of globalization